Chile : 2006 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report ;, 2006)
Structural reforms and prudent economic policies have helped Chile's successful economic performance. Executive Directors commended the sound macroeconomic policies, the structural fiscal surplus rule, and the robust financial system. They appreciated Chile's monetary policy stance and its leadership role in opening markets through comprehensive and sustained trade and financial market liberalization. They welcomed the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CLT) legislation that helps in obtaining information and combating money laundering, and also emphasized the need for a policy agenda for sustained growth.